Requirements engineering: Foundation for Software Quality: 25th International Working Conference, REFSQ 2019, Essen, Germany, March 18–21, 2019, Proceedings - Knauss, Eric; Goedicke, Michael (Programming and Software Engineering, 2019)
Automated Analysis -- Making Sense of Requirements -- Tracelink Quality -- Requirements Management (Research Previews). –From Vision to Specification -- Automated Analysis (Research Previews) -- Requirements Monitoring -- Open Source -- Managing Requirements Knowledge at a Large Scale -- in Situ/Walkthroughs (Research previews)